Strength versus ductility in carbon nanotube reinforced nickel matrix nanocomposites - Borkar, Tushar; Hwang, Jaewon; Hwang, Jun Yeon; Scharf, Thomas W.; Tiley, Jaimie; Hong, Soon Hyung; Banerjee, Rajarshi (CAMBRIDGE UNIV PRESS, 2014)
Two types of carbon nanotube reinforced nickel (CNT/Ni) nanocomposites were processed, both involving spark plasma sintering (SPS) of precursor powders consisting of nickel and carbon nanotubes. The first type involved simple mechanical dry milling of nickel and CNT powders, followed by sintering using SPS, resulting in nanocomposites exhibiting a tensile yield strength of 350 MPa (about two times that of SPS processed monolithic nickel with a strength of 160 MPa) and about 30% elongation to failure. In contrast, the nanocomposites processed by SPS of powders prepared by molecular-level mixing (MLM) exhibited substantially higher tensile yield strength of 690 MPa but limited ductility with an 8% elongation to failure. While the former type of processing involving dry-milling is expected to be lower in cost as well as easy to scale-up, the latter type of processing technique involving MLM leads to a more homogeneous distribution of nanotubes, leading to extraordinarily high strength levels.
Keywords: MECHANICAL-PROPERTIES; THERMAL-PROPERTIES; COMPOSITES; HARDNESS; INTERFACE; GRAPHENE; COPPER